1994
DOI: 10.1002/jcp.1041580102
|View full text |Cite
|
Sign up to set email alerts
|

Migratory and proliferative effect of platelet‐derived growth factor in rabbit retinal endothelial cells: Evidence of an autocrine pathway of platelet‐derived growth factor

Abstract: Angiogenesis is a crucial event in the progression of diabetic retinopathy. Migration and proliferation of endothelial cells (EC) are important steps in angiogenesis and are caused by angiogenic factors such as basic fibroblast growth factor (bFGF). In this work, capillary EC were isolated from rabbit retinal tissues and rabbit retinal EC (RREC) were found to secrete a migration factor for RREC in conditioned medium (CM). The activity was inhibited by an anti-platelet-derived growth factor (PDGF) antibody, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…The endothelium is the production site for several factors with the ability to stimulate or inhibit endothelial cell function (McPherson et al 1981, Schweigerer et al 1987, Koyama et al 1994, Nomura et al 1995. Autocrine regulation provides an insight into the mechanism by which local differences of cell growth and differentiation are established within a capillary microenvironment that would determine, for example, the selection of a single endothelial cell to initiate a new capillary network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelium is the production site for several factors with the ability to stimulate or inhibit endothelial cell function (McPherson et al 1981, Schweigerer et al 1987, Koyama et al 1994, Nomura et al 1995. Autocrine regulation provides an insight into the mechanism by which local differences of cell growth and differentiation are established within a capillary microenvironment that would determine, for example, the selection of a single endothelial cell to initiate a new capillary network.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells are known to produce and respond to their own angiogenic and anti-antiangiogenic factors, and thus exert an autocrine control of neovascularisation (McPherson et al 1981, Schweigerer et al 1987, Koyama et al 1994, Nomura et al 1995. Recent work has suggested that PRLs may contribute to this autocrine regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The endothelium is the production site for several factors with the ability to stimulate or inhibit the formation of new blood vessels (McPherson et al 1981, Schweigerer et al 1987, Klagsbrun & D'Amore 1991, Auerbach & Auerbach 1994, Koyama et al 1994, Nomura et al 1995. Autocrine angiogenic and antiangiogenic factors provide an insight into the mechanisms by which endothelial cell growth is selectively supported or prohibited locally within a tissue microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover endothelial cells produce and respond to their own angiogenic or antiangiogenic factors (autocrine regulation). Endothelial peptides with autocrine effects include basic fibroblast growth factor (bFGF), plateletderived growth factor (PDGF), vascular endothelial growth factor (VEGF) and thrombospondin (McPherson et al 1981, Schweigerer et al 1987, Koyama et al 1994, Nomura et al 1995. Autocrine regulation could help explain the local differences of cell growth and differentiation that must be established in a capillary microenvironment and that are involved, for example, in the selection of a single endothelial cell to initiate a capillary network.…”
Section: Introductionmentioning
confidence: 99%
“…229,230 Additionally, significantly elevated concentrations of PDGF AB are found in the vitreous and preretinal membranes of patients with proliferative diabetic retinopathy (PDR). 231 PDGF may act directly on endothelial cells 232 that are engaged in angiogenesis or that express PDGF receptor beta-subunits. 233,234 However, it is reported that PDGF AB is also elevated in ischemic non-diabetic retinopathy, indicating that ischemia rather than diabetes per se might be a strong stimulator of PDGF production in the retina.…”
mentioning
confidence: 99%